2022
DOI: 10.1021/acsnano.2c08679
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and Strong Ceramic Network with Exceptional Damage Tolerance

Abstract: Lightweight materials such as porous ceramics have attracted increasing attention for applications in energy conservation, aerospace and automobile industries. However, porous ceramics are usually weak and brittle; in particular, tiny defects could cause catastrophic failure, which affects their reliability and limits the potential use greatly. Here we report a SiC/SiO 2 nanowire network constructed from numerous well-bonded SiC nanowires coated by a biphasic structure consisting of amorphous SiO 2 and nanocry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…[82][83][84][85] Herein, considering the rapid development and increasing demands for optimization of the mechanical properties of the present resilient ceramic aerogels for various application situations, this paper mainly focuses on the strategies used to improve mechanical properties based on our previous works related to one-dimensional nanostructures-based resilient ceramic aerogels (SiC nanowire aerogels and Si 3 N 4 nanobelt aerogels). 56,59,[86][87][88][89][90][91][92]…”
Section: Introductionmentioning
confidence: 99%
“…[82][83][84][85] Herein, considering the rapid development and increasing demands for optimization of the mechanical properties of the present resilient ceramic aerogels for various application situations, this paper mainly focuses on the strategies used to improve mechanical properties based on our previous works related to one-dimensional nanostructures-based resilient ceramic aerogels (SiC nanowire aerogels and Si 3 N 4 nanobelt aerogels). 56,59,[86][87][88][89][90][91][92]…”
Section: Introductionmentioning
confidence: 99%
“…For example, Qu et al prepared SiC@SiO 2 NWs by oxidizing SiC NWs in air at high temperatures (900–1200 °C) and found that SiC@SiO 2 NWs showed better thermal insulation properties than SiC NWs . Lu et al prepared SiC@SiO 2 NWs networks by CVD and subsequent heat treatment at 1200 °C, which have potential for engineering applications in harsh environments owing to their lightweight (360 ± 10 mg cm –3 ), high mechanical strength (compressive strength of 16 MPa), and damage resistance . However, considering the growing global energy demand and the depletion of fossil fuel resources, these methods undoubtedly contribute to increased costs and energy consumption. , …”
Section: Introductionmentioning
confidence: 99%
“…22 Lu et al prepared SiC@ SiO 2 NWs networks by CVD and subsequent heat treatment at 1200 °C, which have potential for engineering applications in harsh environments owing to their lightweight (360 ± 10 mg cm −3 ), high mechanical strength (compressive strength of 16 MPa), and damage resistance. 23 However, considering the growing global energy demand and the depletion of fossil fuel resources, these methods undoubtedly contribute to increased costs and energy consumption. 24 In contrast, thermal evaporation of Si powders for synthesis of SiC@SiO 2 NWs has advantages of low production cost, a simple process, environmental friendliness, less impurities in the product, and a controllable NWs structure; therefore, this method is conducive to large-scale synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to the inherent brittleness, HfC coating cannot meet the service requirements of thermal structural components of aerospace vehicles solely relying on its own thermal protection ability. Aiming at this issue, some scholars proposed that introducing nanowires as reinforcements into ceramic to enhance toughness 25,26 . Ren 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at this issue, some scholars proposed that introducing nanowires as reinforcements into ceramic to enhance toughness. 25,26 Ren. 27 introduced HfC nanowires (HfC nws ) into HfC coating, finding that the fracture toughness of the coating was significantly optimized under quasi-static loading.…”
Section: Introductionmentioning
confidence: 99%